(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
Emerging economies have a key aspect in common: their inherent political uncertainty. Therefore, it is critical to understand how firms that operate in this type of economies understand their present environment, if they are to foresee future developments. The scenario planning approach can be used to develop dynamic capabilities to cope with political uncertainty. The purpose of this study is to validate the Oxford Scenario Planning Approach (OSPA) from an emerging economy perspective. To do so, in-depth interviews with members of key business leadership associations (local and foreign) were carried out to discover underlying perceptions that provide insights into future situations. Using ten in-depth interviews with opinion leaders and senior mining executives in Peru, the study shows that corporate planning in this emerging economy is still dominated by short-term, quantitative “forecast-centered” routines that leave firms reactive to shocks and vulnerable to a high-uncertainty trap. Participants recognized that the OSPA could help them to identify and rehearse intangible threats—especially political risk and social conflict—while nurturing three dynamic capabilities: deeper multidimensional risk analysis, faster adaptability, and sharper environmental scanning.